Modern approaches to visual rehabilitation of patients with neuromotor disorde - O. V. Pisarevskaya; L. N. Bachaldina; M. A. Gasparyan (Acta Biomedica Scientifica, 2022)
Background. Approximately 50 % of children with cerebral palsy have vision problems, manifested in strabismus, impaired eye mobility, refractive errors, nystagmus development and partial atrophy of the optic nerve.The aim: to present a clinical case of combined correction of myopia and divergent strabismus in a patient with cerebral palsy (CP).Materials and methods. A clinical case of combined correction of myopia and divergent strabismus in a patient with cerebral palsy is presented. General anesthesia was used to perform a two-stage treatment under one anesthesia: the first stage – laser myopia correction by femtosecond extraction of the lenticule through a small access (SMILE) to both eyes, the second stage was the strabismus correction by performing tenoscleroplasty of the external rectus muscle and resection of the internal rectus muscle of both eyes. The sequence of stages is due to the relative traumatism of strabismus surgery, in some cases, accompanied by a reaction from the bulbar conjunctiva and the cornea in the form of edema, which, during subsequent femtosecond vision correction, can affect the refractive result and worsen visual acuity in the postoperative period.Results. The performed treatment let significantly increase uncorrected visual acuity, achieve a correct and stable eye position, which became the basis for changing the vision nature from monocular to binocular.Conclusion. Thus, modern laser and surgical technologies in combination with an adequate anesthesia allow rehabilitating patients as much as possible in a short time, even with severe forms of cerebral palsy, and significantly improving the quality of life.